Cyberpolitics in International Relations - Nazli Choucri (The MIT Press, 2012)
Cyberspace is a fact of daily life. Because of its ubiquitous nature and vast scale and scope, cyberspace — including the Internet and the hundreds of millions of computers the Internet connects, the institutions that enable it, and the experiences it enables — has become a fundamental feature of the world we live in and has created a new reality for almost everyone in the developed world and for rapidly growing numbers of people in the developing world. 1 Until recently, cyberspace was considered largely a matter of low politics — a term used to denote background conditions and routine decisions and processes. By contrast, the matters of interest in high politics have to do with national security, core institutions, and decision systems critical to the state, its interests, and its underlying values. 2 Nationalism, political participation, political contentions, conflict, violence, and war are among the common concerns of high politics. 3 But low politics do not always remain below the surface. If the cumulative effects of normal activities shift the established dynamics of interaction, then the seemingly routine can move to the forefront of political attention. When this happens, it can propel the submerged features into the political limelight. In recent years, issues connected to cyberspace and its uses have vaulted into the highest realm of high politics. We now appreciate that cyberspace capabilities are also a source of vulnerability, posing a potential threat to national security and a disturbance of the familiar international order. 4 The global, often nontransparent interconnections afforded by cyberspace have challenged the traditional understanding of leverage and influence, international relations and power politics, national security, borders, and boundaries — as well as a host of other concepts and their corresponding realities. Many features of cyberspace are reshaping contemporary international relations theory, policy, and practice. Those related to time, space,permeation, fluidity, participation, attribution, accountability, and ubiquity are the most serious ( table 1.1) . Individually, each feature is at variance with our common understanding of social reality and with contemporary understandings of international relations. Jointly, they signal a powerful disconnect.